Optimisasi Manajemen Material Konstruksi dengan Pendekatan Just In Time - Monika Tiku Padang; Josefine Ernestine Latupeirissa; Helen Adry Irene Sopacua (Paulus Civil Engineering Journal, 2025)
The Just In Time (JIT) method is a method to save inventory and material storage costs in storage warehouses by supplying the required materials from suppliers on time. Therefore, the application of construction material management using the JIT method in a project is very important to help reduce material storage and procurement costs. By reducing the amount of materials stored at the project site, the company can save on storage costs and reduce the possibility of damage or loss of materials. This study of the JIT method was carried out on the construction of the regional office building of the Directorate General of Customs and Excise of South Sulawesi, to find out how the application of JIT can optimize construction material management. In The method used in this research is a comparison technique, namely by comparing material inventory management practices at the project site. comparing material inventory management practices at the project site with using JIT principles using primary data, namely observation and interviews while secondary data is logistical data. The results show that the JIT inventory management method is not applied in material inventory in the construction project of the regional office building of the Directorate General of Customs and Excise of South Sulawesi. In this study, material ordering that applies the JIT approach is known to optimize material management in the implementation of construction projects, so that there are no delays that can hinder work.